Understanding parental hesitancy toward children's COVID-19 vaccinations: The influence of government, media and interpersonal communication - Clayton, Carmen; Clayton, Rafe; Al-Azri, Sultan; Mogeh, Ileyas; Potter, Marie (Frontiers in Communication, 2023)
In March 2022, the UK Health Security Agency and the National Health Service issued guidance for parents of children aged 5-11 concerning vaccinations. The guidance stated that parents of all children in this age bracket should be offered the chance to have their child vaccinated and that the procedure was particularly important for children who have health conditions that put them at high risk. However, expressions of child vaccine hesitancy rose steeply in the UK at the start of 2022 with 35.4% of primary school parents saying they were unlikely to vaccinate their children. Vaccination programmes are part of the global strategy for mitigating the effects of coronavirus disease, but their effectiveness is reliant upon high levels of uptake and administration. Vaccine hesitancy, for children in particular is an important concern, given that children can play a major role in coronavirus transmission within both families and schools. Listening to parental perspectives regarding the decision-making processes for vaccinating this age group, becomes fundamental in understanding childhood vaccine intentions. Through the analysis of semi-structured interviews, this paper is able to reveal detailed qualitative insights into the thoughts of UK parents and their attitudes towards children’s vaccinations that quantitative statistics are otherwise unable to show. In the following article, we have identified a triangular relationship between government, media and interpersonal communication in shaping parental perspectives, leading to a mixture of both ‘pro-vax’ and ‘anti-vax’ attitudes [often simultaneously] in regards to the vaccination or non-vaccination of children. Our data provides original findings that will inform both policymakers and practitioners, building upon and extending the existing vaccination literature, furthering current debate and guiding future research.